Climate Change Reduces Darling River Water Levels by Decreasing Eastern Australian Rainfall - Milton S. Speer; Lance M. Leslie (Journal of Water, 2024)
Significantly decreased rainfall run-off into the dams that feed the Darling River in eastern Australia during the Millennium (1997–2009) and Tinderbox (2017 –2019) Droughts coincided with reduced river levels along the Darling River. The rainfall reduction was due to accelerated global warming since the mid-late 1990s. During this period, unmonitored river water extraction from the streams that feed the Darling River was diverted to crops, on-farm dams, and to storage in the Menindee Lake system. This practice exacerbated the effect of the two droughts because streamflow that reaches the Darling River ceased in several upstream rivers, and in the Darling River. Using Darling River height levels, before and after the mid-late 1990s, it is shown that global warming is the key factor reducing Darling River levels in the last 53 years, even allowing for river water diversion and extraction. Between the periods 1972-1997 and 1998-2024 the Darling River mean heights, in the towns of Bourke, Wilcannia and Menindee, were all found to drop by statistically significant amounts. The catchment area rainfall has found to be decreasing due to global warming induced atmospheric circulation changes. Reducing water extraction either before or after it reaches the Darling River is unlikely to stop the short-medium term decline in Darling River levels.
Keywords: Darling River